Uterine Mycotic Flora in Healthy Buffaloes and Buffaloes with Reproductive Disorders - Ismail, Salmah; Chavoshi, M.; Hussaini, J.; Malekshaabani, S. (Marsland Press, 2014)
Buffalo’s uterine mycotic flora has not been studied too much yet. The aim of current study is to investigate fungi in uterine of healthy buffaloes with the history of uterine disorders like metritis. Uterine lavage was done in 100 buffaloes (50 healthy and 50 problematic). Samples were cultured in Subro Glucose agar medium and Chloramphenicol in 28°C for 2 weeks. For more identification of fungi, Corn Meal Tween 80 agar medium and Chapex dox agar were used. The data were analyzed by Chi-square test in SPSS software. Fungi colonies were isolated from 20% (10) and 26% (13) of healthy and problematic buffalo cows, respectively and the difference was significant (p<0.05). The most prevalent fungi in buffaloes with uterine disorders were Aspergillus fumigatus and Penicillium spp., respectively. Mucur was dominant in healthy uterine. Uterine disorders may predispose uterine mycotic infections in buffaloes and lead to subfertility.